Mycogenic silver nanoparticles from endophytic trichoderma atroviride with antimicrobial activity - Abdel-Azeem, Ahmed; Nada, Amr A.; O’Donovan, Anthonia; Thakur, Vijay Kumar; Elkelish, Amr (Tech Science Press, 2020)
There is an increasing interest in developing nanoparticles with diverse biologic activities. To this end, we prepared 10 to 15 nm silver nanoparticles (AgNP) from native isolates of Trichoderma atroviride. Within this study, endophytic fungi hosted four medicinal plants in Saint Katherine Protectorate, South Sinai, Egypt have been isolated by surface sterilization technique on four isolation media. Ten species, based on their frequency of occurrence, out of twenty recovered taxa were tested for their capability to synthesize extracellular AgNPs. Trichoderma atroviride hosted Chiliadenus montanus was found to be the best candidate for the production of mycogenic AgNPs among all examined species. The mycosynthesized AgNPs were compared with chemically synthesized and characterized using Ultraviolet-visible (UV-vis) spectroscopy, Raman spectroscopy, X-ray diffraction (XRD) and high-resolution transmission electron microscopy (HRTEM) techniques. The HRTEM result showed the distribution of spherical AgNPs ranging from 10 to 15 nm. Trichoderma atroviride isolate was subjected to sequencing for confirmation of phenotypic identification. The internal transcribed spacer (ITS) 1–5.8 s – ITS2 rDNA sequences obtained were compared with those deposited in the GenBank Database and registered with accession number MH283876 in the NCBI Database. Antibacterial, anticandidal and antifungal effects of chemically and mycosynthesized AgNPs were examined at various concentrations in vitro against six pathogenic bacteria and 4 pathogenic fungi by agar well diffusion technique. Standard antibiotics; Gentamicin, Amoxicillin, Clotrimazole, and Nystatin at 5 μg/disk were taken as positive controls, while 5% DMSO was used as the negative control. Our data revealed that the application of mycogenic AgNPs at a concentration of 100 ppm resulted in maximum inhibition of pathogenic bacteria and fungi. These data suggest that AgNPs from native isolates of Trichoderma atroviride (MH283876) offer a source of rapid synthesis of eco-friendly, economical biomaterials that show antimicrobial activities.
Keywords: Antimicrobial; Endobionts; Mycogenic AgNPS; Saint Katherine Protectorate